Memorie di Adriano: ritratto di una voce da Marguerite Yourcenar a Maurizio Scaparro - Paolo Bosisio (Lanx, 2011)
Memorie di Adriano, a play staged by Maurizio Scaparro in 1989 in the setting of Hadrian’s Villa, offers a major example of dramaturgy based on a non-dramatic source, a kind of drama more and more common nowadays, but quite unusual for a renowned director. Nonetheless, the play represents a coherent example of Scaparro’s peculiar dramatic research.